A Note on the Athenian Hiereus of Drusus Hypatos - Camia, Francesco (Tekmeria, 2013)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 10.0pt; font-family: Gentium; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; letter-spacing: -.1pt; mso-ansi-language: EN-GB; mso-fareast-language: EL; mso-bidi-language: AR-SA;" lang="EN-GB">A cult for Drusus the Elder was instituted in Athens following Drusus’ death in 9 BC. In inscriptions the priest of this cult is referred to as “hiereus of Drusus hypatos”. This priestly office was associated with the charge of eponymous archon, as shown by the fact that all preserved Athenian laterculi archontum dated after 9/8 BC mention the priesthood of the consul Drusus next to the office of archon. Based on the analysis of the epigraphic references (around twenty) to the priesthood of the consul Drusus one can argue that the latter disappeared sometime between ca. AD 105 and 140. At the end of the 19th century Dittenberger had stated that the proliferation of honours for the emperor Hadrian following his first official visit to the city (AD 124/5) would have finally provoked the end of Drusus’ priesthood. Indeed, the cult of Drusus must not have survived beyond Hadrian’s reign, yet I hypothetically suggest that Hadrian’s visit as a privatus in 111/2 AD, when the future emperor was offered the eponymous archonship without apparently holding the office of priest of Drusus, may have been the first act of its disappearance. I suggest that for reasons of convenience in that year the office of hiereus of Drusus hypatos may have not been held, and this event could have brought about the end of this priesthood, either immediately or gradually over the following years.<!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--><!--[if gte mso 10]> <![endif]-->